Prevalence of posterior vitreous detachment in glaucoma patients and controls. Issue 3 (14th December 2016) - Schwab, Christoph; Glatz, Wilfried; Schmidt, Bernd; Lindner, Ewald; Oettl, Karl; Riedl, Regina; Wedrich, Andreas; Ivastinovic, Domagoj; Velikay‐Parel, Michaela; Mossboeck, Georg
Abstract: Purpose: To evaluate the impact of oxidative stress – present in glaucoma – on the vitreous. We therefore compare the presence of early and late stages of posterior vitreous detachment (PVD) between patients with glaucoma and controls. Methods: The vitreous state was evaluated by the combination of optical coherence tomography and ultrasound. The main outcome was the vitreous state classified into 'no PVD', 'initial PVD' and 'advanced PVD'. Results: We evaluated the vitreous state in 48 patients with glaucoma (age: mean 66.5 ± 11.9 years; visual field deviation: mean 10.4 ± 6.8 dB) and compared the results with 101 previously investigated controls (age: mean 73.6 ± 9.3 years). After one‐to‐one matching on age and sex, ordinal logistic regression revealed that patients with glaucoma were significantly more likely to exhibit advanced PVD stages compared to non‐glaucoma patients (OR 2.60, 95% confidence interval: 1.06–6.36, p = 0.037). Conclusion: Our results suggest that the presence or absence of PVD might be a valuable hint for diagnosing glaucoma – however, further research is needed to determine whether PVD can be used to supplement current glaucoma screening guidelines.